Sistem Pendukung Keputusan Seleksi Karyawan Untuk Jabatan Kepala Koki Menggunakan Metode MOORA - Darwis, Darwis (Journal Global Technology Computer, 2024)
Food and beverage sales are the second largest source of revenue after room sales. Therefore, maintaining food quality is very necessary to achieve guest satisfaction. This study aims to determine the duties and responsibilities of food and beverage products, to determine the standard operating procedures of food and beverage products, and to find out how the role of the head chef in maintaining food quality at NIvia Hotel Medan. The role of the head chef in maintaining food quality is very important in the world of hospitality. The head chef's role can be done by carrying out the food production process in accordance with predetermined recipe standards, carrying out food production activities in accordance with predetermined standard operating procedures, coordinating with waiters/ss in food preparation and serving, maintaining and ensuring all equipment and food production areas are always clean, hygiene and sanitation cook. All of that needs to be done because a quality product will result in guest satisfaction. Therefore, this research is intended to build an application, where the owners are facilitated in the process of selecting employees for the position of head chef at nivia Hotel Medan using the moora method and with criteria that must be met by employees.